ANALYSIS OF THE RUSSIAN PRIMARY DRUG ABUSE PREVENTION SYSTEM AND PROPOSALS FOR ITS OPTIMIZATION - V. A. Korshunov; A. Ya. Mindlina; Yu. E. Vjazovichenko (Сеченовский вестник, 2016)
The article presents the аnalysis of the Russian primary drug abuse prevention system and proposals for its optimization. We found that the primary drug abuse prevention system in use ieﬃcient and the programs are incomprehensive, unadapted, inconsistent and do not have universal coverage.The preventive component is included in the school's extracurricular activities but the classes are not held on a regular basis. The article presents the results of the survey of the senior students in the two Moscow universities. The surveyt rebealed low awareness of thq adverse health eﬀect of drug abuse and high willingness to try drugs. The article proposes the ways to optomize primary drug abuse prevention system.